Respuesta :

Answer:

[tex]f^{-1}[/tex](x) = [tex]\frac{x-3}{2}[/tex]

Step-by-step explanation:

Let y = f(x) and rearrange making x the subject

y = 2x + 3 ( subtract 3 from both sides )

y - 3 = 2x ( divide both sides by 2 )

[tex]\frac{y-3}{2}[/tex] = x

Change y back into terms of x, hence

[tex]f^{-1}[/tex](x ) = [tex]\frac{x-3}{2}[/tex]

Keep in mind that f(x) means the same thing as y so...

y = 2x + 3

To find the inverse operation you switch the places of x and y like so...

x = 2y + 3

Now you must solve for y. To start off you must subtract 3 to both sides.

x - 3 = 2y + 3 - 3

x - 3 = 2y

Now divide 2 to both sides to completely isolate y

(x - 3) / 2 = 2y / 2

[tex]\frac{1}{2} x - \frac{3}{2}[/tex] = y

OR

[tex]\frac{x}{2} -\frac{3}{2}[/tex] = y

Hope this helped!

~Just a girl in love with Shawn Mendes